Computer Vision Syndrome among undergraduate dentistry students - Bartoszek, Adrian; Szalast, Kamil; Kardas, Grzegorz (Journal of Education, Health and Sport, 2019)
Introduction The computer has become a common device and an indispensable tool not only in office but also in everyday life. As a consequence of working at the computer, Computer Vision Syndrome (CVS) may develop. The prevalence of CVS is estimated from 64% to 90% among computer users. Symptoms of the syndrome may be divided into ocular, visual and musculoskeletal. Aim The aim of the study was to evaluate the prevalence of CVS symptoms among dentistry students and to determine the factors associated with the syndrome. Material and methods The study involving 62 students from the dentistry of Medical University was conducted. Students were invited to complete a self-administered questionnaire regarding socio-demographic data and CVS-related questions. Results Among dentistry students, most often CVS symptoms are headache, eye strain and neck pain. Headache, double vision and shoulder pain was significantly associated with gender. Conclusion Dentistry students suffer from CVS. Due to the increase of computer use in the last few years the syndrome is at risk of becoming a major public health issue. Treatment of the syndrome focuses primarily on prevention, which is the modification of the computer environment and user education.